CEO Inside Debt and Accounting Conservatism - Wang, Cong; Xie, Fei; Xin, Xiangang (Contemporary Accounting Research, 2018)
ABSTRACT We examine the relation between accounting conservatism and inside debt held by managers in the form of pension benefits and deferred compensation. We find that financial reporting is less conservative in firms whose CEOs hold more inside debt, particularly in firms with high default risk and agency costs of debt. This is consistent with our hypothesis that by aligning managerial incentives more closely with those of debtholders, inside debt reduces debtholders’ expropriation concerns and thus their demand for accounting conservatism. Our results are robust to identification strategies addressing the endogeneity of CEO inside debt and to alternative measures of accounting conservatism.